Welding defects, Causes and their Remedies: A Review: welding defects - Rizvi, Saadat Ali; Alib, Wajahat (Teknomekanik, 2019)
This review paper looks at the causes of welding defects and their remedies which occur during the welding process. Welding industries in developing countries bearing poor quality and productivity due to the involvement of a number of the process parameter. Even in a completely controlled process, defects in the welding are observed and hence welding process is also known as the process of uncertainty which challenges explanation about the cause of welding defects. In order to identify the welding defect and problem-related to welding, the study is aimed at the research work. This will be beneficial in enhancing the yield of welding. Beside this, standardization (optimization) of process parameter for the entire cycle of manufacturing of the critical part is intended in the proposed work .This review paper also provides the accurate guideline to the quality control department to find welding defects and will help them to analyze defects which are not desired. In this review paper, an attempt has been made to categorise the various welding defects and their root causes of happening.